Employee Performance and Work Motivation - Steiva Amerlien Sandra Wowiling; Frangky Turang (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to investigate the effects of work discipline and motivation on the output of KFC Bandung employees. The descriptive quantitative method is used in this investigation. The results of the aforementioned study indicate that employee performance at KFC Bandung is positively impacted by job motivation. Despite the fact that great performance may aid an organisation in achieving its objectives. At KFC Bandung, employee performance is significantly impacted by job satisfaction. This illustrates that an employee's performance improves in direct proportion to their level of job discipline. Workplace rules seldom ever have an impact on how well employees at KFC Bandung perform. When employees lack discipline, businesses find it difficult to achieve perfect results. Discipline fosters a strong work ethic since it moulds employees' personalities.